2008
DOI: 10.1056/nejmra0802714
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer

Abstract: T h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 359;13 www.nejm.org september 25, 2008

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
1,942
1
23

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,288 publications
(2,022 citation statements)
references
References 122 publications
21
1,942
1
23
Order By: Relevance
“…[221][222][223] The discovery of other molecular resistance aberrations, such as MET kinase amplification or mutations of EML4-ALK fusion, which cause constitutive activation of RAS/RAF1/MAP2K1, has provided further insight and validation into factors limiting the therapeutic efficacy of EGFR inhibitors. 53,148,224 The mystery as to why all tumors harboring drug-sensitive EGFR mutations do not respond to treatment with EGFR TKI inhibitors is yet to be resolved. Clinical investigations have shown that the presence of other genetic alterations affecting signaling pathways downstream of EGFR may have a crucial role.…”
Section: Other Genomic Alterationsmentioning
confidence: 99%
“…[221][222][223] The discovery of other molecular resistance aberrations, such as MET kinase amplification or mutations of EML4-ALK fusion, which cause constitutive activation of RAS/RAF1/MAP2K1, has provided further insight and validation into factors limiting the therapeutic efficacy of EGFR inhibitors. 53,148,224 The mystery as to why all tumors harboring drug-sensitive EGFR mutations do not respond to treatment with EGFR TKI inhibitors is yet to be resolved. Clinical investigations have shown that the presence of other genetic alterations affecting signaling pathways downstream of EGFR may have a crucial role.…”
Section: Other Genomic Alterationsmentioning
confidence: 99%
“…The 5‐year survival rates for lung cancer in 2005–2009 ranged from 15% to 20% in most countries (Cheng et al., 2016; Wang et al., 2013). Non‐small cell lung cancer (NSCLC) is the most common histological type, comprising approximately 80%–85% of cases (Herbst, Heymach, & Lippman, 2008; Reck, Heigener, Mok, Soria, & Rabe, 2013). While the distribution of histologies varies among countries, the two most common NSCLC histological subtypes are squamous cell carcinoma and the non‐squamous cell carcinomas, of which adenocarcinoma is the most common.…”
Section: Introductionmentioning
confidence: 99%
“…The high mortality of NSCLC is largely attributable to late diagnosis, when metastases are present. 2 The molecular mechanisms governing metastasis of NSCLC remain poorly understood.Metastasis is a complex, multistep process, involving migration and invasion of malignant cells from the primary tumor to blood vessels, intravasation, and survival in the circulation, and ultimately extravasation, colonization, and formation of secondary tumor at distant target organs. 3 Each of these events is classically driven by the acquisition of genetic and/or epigenetic traits in tumor cells and the cooperation of nonneoplastic stromal cells.…”
mentioning
confidence: 99%
“…1 Non-small-cell lung cancer (NSCLC) accounts for~80-85% of lung cancers. 2 Only 20-30% of NSCLC are radically resectable and the majority of lung cancer patients succumb to the disease. The high mortality of NSCLC is largely attributable to late diagnosis, when metastases are present.…”
mentioning
confidence: 99%
See 1 more Smart Citation